Comprehension of written sentences as a core component of children's reading comprehension. (6th May 2011) - Ecalle, Jean; Bouchafa, Houria; Potocki, Anna; Magnan, Annie
<x xml:space="preserve">Abstract</x> Two experiments were conducted to test the hypothesis that sentence processing is an essential mediatory skill between word recognition and text comprehension in reading. In Experiment 1, a semantic similarity judgement task was used with children from Grade 2 to Grade 9. They had to say whether two written sentences had the same (or very similar) meanings or whether the meanings of the two sentences were very different. As expected, performance improved with age both on the high‐frequency words and with increasingly complex sentences. In Experiment 2 with children in Grade 3, scores in written sentence comprehension and vocabulary made the most important unique contribution to the reading comprehension of an expository text. The results are discussed first, in the light of a general framework in which sentence‐level skill is at the core of reading comprehension and second, with reference to the issue of reading assessment.